Epidemiological Differences Between Localised And Non-Localised Low Back Pain - Coggon, D.; Ntani, G.; Walker-Bone, K.; Palmer, K. T.; Felli, V. E.; Harari, R.; Warnakulasuriya, S.S.P (My University, 2017)
Study design—Cross-sectional survey with longitudinal follow-up Objectives—To test the hypothesis that pain which is localised to the low back differs epidemiologically from that which occurs simultaneously or close in time to pain at other anatomical sites Summary of Background Data—Low back pain (LBP) often occurs in combination with other regional pain, with which it shares similar psychological and psychosocial risk factors. However, few previous epidemiological studies of LBP have distinguished pain that is confined to the low back from that which occurs as part of a wider distribution of pain. Methods—We analysed data from CUPID, a cohort study that used baseline and follow-up questionnaires to collect information about musculoskeletal pain, associated disability and potential risk factors, in 47 occupational groups (office workers, nurses and others) from 18 countries. Results—Among 12,197 subjects at baseline, 609 (4.9%) reported localised LBP in the past month, and 3,820 (31.3%) non-localised LBP. Non-localised LBP was more frequently associated with sciatica in the past month (48.1% vs. 30.0% of cases), occurred on more days in the past month and past year, was more often disabling for everyday activities (64.1% vs. 47.3% of cases), and had more frequently led to medical consultation and sickness absence from work. It was also more often persistent when participants were followed up after a mean of 14 months (65.6% vs. 54.1% of cases). In adjusted Poisson regression analyses, non-localised LBP was differentially associated with risk factors, particularly female sex, older age and somatising tendency. There were also marked differences in the relative prevalence of localised and non-localised LBP by occupational group. Conclusions—Future epidemiological studies should distinguish where possible between pain that is limited to the low back and LBP which occurs in association with pain at other anatomical locations.
Keywords: Low back pain; diagnostic classification; epidemiology; disability; medical consultation; sickness absence; sciatica; risk factors; somatising; occupation; prognosis